Maternal and Birth History Risk Factors of Stunting Among Underfive Children in Demak Regency, Central Java, Indonesia - Pradigdo, Siti Fatimah; Kartasurya, Martha Irene; Suyatno; Naintina Lisnawati (Universitas Airlangga, 2026)
In Indonesia, stunting remains a public health problem, with a prevalence of > 20%. The objective of this study was to find the determinants of under five children stunting in family characteristics, maternal factors, birth history, and environmental factors. This case-control study was conducted on 1,093 children in ten villages with high stunting rates in Demak District based on stunting loci from the Ministry of Health. A total of 537 stunted children and 556 non-stunted children were found. Data were collected through structured interviews, maternal and child health cards, and anthropometric measurements of children using an infantometer, stadiometer, and digital weighing scales, conducted by trained personnel. The data were analyzed using Chi Square, and multiple logistic regression. Factors associated with stunting were: number of children (OR=1.441; CI 95%= 1.096-1.895), child food expenditure (OR=1.379; CI 95%= 1.087-1.750), Maternal height (OR=2.633; CI 95%=1.994-3.478), MUAC (p=0.04; OR=1.350; CI 95%=1.013–1.798), maternal knowledge (OR=1.630; CI 95%=1.262–2.105), complementary feeding (OR=1.387; OR 95%=1.087–1.771), Birth weight (OR=2.178; CI 95%=1.397–3.396). Birth length (1.638; CI 95%=1.263-2.125). Upper respiratory tract infection (OR=1.302; 95% CI=1.023 – 1.658). The main determinants of stunting were the number of children >2, low birth weight, low expenditure for child' food, upper respiratory tract infection, stunted mother and early complementary feeding.